Chronic meningococcemia: a rare presentation of meningococcal disease: case report - Brandão, Antonio Adolfo Guerra Soares; Prokopowitsch, Aleksander Snioka; Campos, Fernando Peixoto Ferraz de; Yoshihara, Liz Andrea Kawabata (Autopsy and Case Reports, 2012)
Chronic meningococcemia is a rare clinical presentation within the spectrumof infections due to Neisseria meningitidis, which was first described in 1902.It is defined as a chronic and benign meningococcal bacteremia withoutmeningeal signs or symptoms with at least one week’s duration, characterizedby intermittent or continuous fever, polymorphic cutaneous rash, and migratoryarthropathy. The incidence is believed to be around 1:200,000 inhabitants. Itaffects predominantly young people and adults, and it is equally distributedbetween genders. Diagnosis may be challenging in the early stages of thedisease because of the difficulty in isolating Neisseria meningitidis (it reaches74% of positivity in advanced stages). Recently, the use of PCR for detectingNeisseria sp antigen in skin biopsies specimens has been considered for thoseculture-negative cases. The authors report a case of a 54-year-old femalepatient who sought medical attention for a five-day fever followed by arthralgiaand skin lesions predominantly in the lower limbs. The patient progressed toa toxemic clinical status that improved after the administration of antibiotictherapy, which consisted of oxacillin and ceftriaxone. The diagnosis of chronicmeningococcemia was performed after the isolation of Neisseria meningitidisin two different blood sample cultures. This is, to our knowledge, the firstcase of chronic meningococcemia described in Brazil (up to the writing of thisreport).